Magma volume and timescales in the formation of porphyry molybdenum deposits: A case study from the Central Asian Orogenic Belt - Zhang, Qiang; Zhang, Zhaochong; Cheng, Zhiguo; Santosh, M.; Wang, Zhenchao; Jin, Shengkai (Lithos, 2021)
Porphyry Mo deposits, as an important repository for molybdenum, are generally considered to have formed from the reworking of Mo-rich ancient crust. However, some of the giant porphyry Mo deposits in the Central Asian Orogenic Belt (CAOB) are thought to have been derived from juvenile crust. Here we evaluate the role of large volume magma chamber,and the timescales of magmatic differentiation and hydrothermal processes in the formation of porphyry Mo deposits. In our case study on the Donggebi porphyry Mo deposit along the southern part of the CAOB, the pressure-temperature conditions of crystallization of the ore-related intrusion are estimated as 1.2–1.8 kbar and 570–727 °C. Based on the sulfur content of apatite grains from the deposit, we estimate that a large magma volume (25–215 km3) was involved in the formation of the Mo resources (0.508 Mt) associated with the Donggebi porphyry Mo deposit. Quartz associated with mineralization in this deposit is identified as two types. Type-1 quartz displays wide and parallel zoning and preserves high Na, K and Ca contents whereas Type-2 displays narrow and subparallel zoning with low Na, K and Ca contents. The Type-1 quartz is likely to retain the magmatic information, whereas the Type-2 quartz possibly formed through metasomatic processes in the hydrothermal stage. We use Ti diffusion patterns in quartz coupled with TitaniQ thermobarometry to estimate the timescales of magma evolution and hydrothermal processes. The quartz residence in the magma chamber is estimated as 10,000 to 40,000 years while that related to hydrothermal fluids is relatively short (800 to 5000 years). Our results suggest that large volume magma chambers might be an essential requisite for the formation of porphyry Mo deposits, as against models that consider prolonged hydrothermal processes. •Prolonged hydrothermal processes are not prerequisite for giant Mo mineralization.•The formation of porphyry Mo deposit is not sensitive to initial oxygen fugacity.•Voluminous reservoir may be a critical factor for large porphyry Mo deposits.